Rationally Designed Hierarchically Structured Tungsten Nitride and Nitrogen-Rich Graphene-Like Carbon Nanocomposite as Efficient Hydrogen Evolution Electrocatalyst - Zhu, Y.; Chen, G.; Zhong, Y.; Zhou, W.; Shao, Zongping (WILEY-BLACKWELL, 2017)
© 2017 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Practical application of hydrogen production from water splitting relies strongly on the development of low-cost and high-performance electrocatalysts for hydrogen evolution reaction (HER). The previous researches mainly focused on transition metal nitrides as HER catalysts due to their electrical conductivity and corrosion stability under acidic electrolyte, while tungsten nitrides have reported poorer activity for HER. Here the activity of tungsten nitride is optimized through rational design of a tungsten nitride-carbon composite. More specifically, tungsten nitride (WN x ) coupled with nitrogen-rich porous graphene-like carbon is prepared through a low-cost ion-exchange/molten-salt strategy. Benefiting from the nanostructured WN x , the highly porous structure and rich nitrogen dopant (9.5 at%) of the carbon phase with high percentage of pyridinic-N (54.3%), and more importantly, their synergistic effect, the composite catalyst displays remarkably high catalytic activity while maintaining good stability. This work highlights a powerful way to design more efficient metal-carbon composites catalysts for HER.